2022
DOI: 10.4103/jfmpc.jfmpc_1964_21
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical pattern and seasonal variation of dermatoses in children: Contemplating findings for family physicians

Abstract: Introduction: Pediatric skin disorders are different from the adult type in their presentations, types, treatment and prognosis. Their presentation varies from place to place. Aim: To study the different clinical pattern and seasonal variation of dermatoses in children attending a multispecialty hospital in Uttar Pradesh. Materials and Methods: This study was conducted among 640 children who attended the OPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…respectively [13,14]. Kandpal et al, also observed males' preponderance in their study [15]. However, different from others who detected females' preponderance in their studies [16,17,18].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…respectively [13,14]. Kandpal et al, also observed males' preponderance in their study [15]. However, different from others who detected females' preponderance in their studies [16,17,18].…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Saini et al [35] [44,27,52]. Deviate from Kandpalr et al [15] who showed that all cases were vitiligo. Disorders of sweat and sebaceous gland constituted (4.2%).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…• Exposición al calor: La exposición prolongada a altas temperaturas, especialmente en climas cálidos y húmedos, puede causar sudoración excesiva, aumentando el riesgo de que las GS se obstruyan y pos consiguiente se desarrolle la LM (15,16). Resulta común en los bebes o niños pequeños, debido a que en lo primeros años de vida no está desarrollada de forma completa su capacidad para regular la temperatura corporal a través de la sudoración.…”
Section: Factores Desencadenantesunclassified